1989
DOI: 10.1002/bio.1170040104
|View full text |Cite
|
Sign up to set email alerts
|

Marlene A. DeLuca (1936–1987)

Abstract: LiFE AND CONTRIBUTION OF MARLENE DELUCA O.M. Smith Lecture a t O k l a h o m a S t a t e University a n dt h e text of this outlined her research as she saw it. An edited version of t h e lecture has appeared in I . Biolumin. Chemilumin. (1989)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…This is the only modern review on this rather unusual glowworm found in the roofs of certain New Zealand caves ! On a more somber note, the journal has also published the obituaries of some workers eminent in the field of bioluminescence, namely Professor Marlene DeLuca (University of California at La Jolla, CA, USA), Professor Gordon Stewart (University of Nottingham, UK) and Dr Jean‐Marie Bassot (CNRS, Paris, France) .…”
Section: Current Awarenessmentioning
confidence: 99%
“…This is the only modern review on this rather unusual glowworm found in the roofs of certain New Zealand caves ! On a more somber note, the journal has also published the obituaries of some workers eminent in the field of bioluminescence, namely Professor Marlene DeLuca (University of California at La Jolla, CA, USA), Professor Gordon Stewart (University of Nottingham, UK) and Dr Jean‐Marie Bassot (CNRS, Paris, France) .…”
Section: Current Awarenessmentioning
confidence: 99%
“…This prize is awarded to symposium participants under the age of 35 and is given in memory of Dr Marlene DeLuca who made major contributions to the science of bioluminescence (4).…”
mentioning
confidence: 99%
“…Starting in 1988 at the meeting in Florence, Italy, the symposia have provided the venue for the award of the Marlene DeLuca prize (generously sponsored by Dr Fritz Berthold). This prize is awarded to symposium participants under the age of 35 and is given in memory of Dr Marlene DeLuca who made major contributions to the science of bioluminescence (4).…”
mentioning
confidence: 99%